مشكلة الفساد الأداري والمالي معوق أساس للأستثمار في العراق - علي عبودي, نعمة الجبوري (جامعة الوادي - University of Eloued, 2019)
الغرض هو معرفة ظاهره الفساد الإداري والمالي الذي يعد من أخطر الظواهر التي تواجه البلدان وعلى الأخص الدول النامية والتي يترتب عليها شلل في عملية البناء والتنمية الأقتصادية بما تنطوي عليه من تدمير الأقتصاد والقدرة المالية والإدارية وبالتالي عجز الدولة على مواجهة تحديات الأعمار وإعادة الأعمار والبنى التحتية اللازمة لذلك. ومن بين هذه المشاكل وأهمها الأثار السلبية على الحياة العامة للشعوب, ومشكلة الفساد الأداري والمالي مشكلة تتباين حدتها وقوتها حسب الدول وحكوماتها وقدرتها على محاربة الفساد والقضاء عليه, ويأتي هذا البحث كمساهمة متواضعة لبيان دور وأهمية حل مشكلة الفساد الأداري والمالي, الأستنتاجات ما كشفته تقارير الدوائر المعنية عن حالات الفساد المالي الواضحة والكبيرة في بعض الوزارات في العراق بسبب غياب سلطة القانون وعدم تفعيل القضاء ومحاسبة الفاسدين, ومن أهم التوصيات هي تفعيل دور المحاسبة القانونية للفاسدين ومن خلال مطالبة الوزارات والدوائر المستقلة ومنشئات القطاع العام بتفعيل الرقابة الداخلية. The purpose is to learn about the phenomenon of administrative and financial corruption ، which is one of the most serious phenomena facing countries ،particularly the developing countries ، which have the potential to paralyse the process of building and economic development ،with the destruction of the economy ،financial and administrative capacity ،and thus the inability of the State to meet the challenges Reconstruction and reconstruction and the necessary infrastructures. Among these problems ،the most important of which are the negative effects on the public life of peoples ، and the problem of administrative and financial corruption ،which vary in severity and strength depending on the countries and their Governments and their ability to fight and eliminate corruption. This research is a modest contribution to the role and importance of solving the problem of administrative and financial corruption. Conclusions the reports of the relevant departments on clear and significant cases of financial corruption in some ministries in Iraq were revealed because of the absence of the rule of law ،the lack of enforcement of the judiciary and the accountability of corrupt people ،and one of the most important recommendations is to activate the role of legal accounting for the losers and by asking the ministries and departments Independent and constructors
مقال
Keywords: الفساد, الاستثمار, الرقابة الداخلية, المحاسبة القانونية